Mechanochemical synthesis of inverse vulcanized polymers - Peiyao Yan; Wei Zhao; Fiona McBride; Diana Cai; Joseph Dale; Veronica Hanna; Tom Hasell (Nature Communications, 2022)
Inverse vulcanization is a process that enables to convert sulfur, a by-product of the petroleum industry, into polymers. Here the authors report a synthetic method of inverse vulcanization via mechanochemical synthesis; compared to thermal routes, a broader range of monomers can be used, and the protocol yields materials with enhanced mercury capture capacity.